Analisis Perilaku Komunikasi Guru dalam Proses Pembelajaran di SD Negeri 20 Dadok Tunggul Hitam - Sya’bani, Silvyna (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Teacher communication is a critical factor for effective learning, particularly at the Primary School level, which demands supportive and empathetic pedagogical interaction. This research aims to analyze the communication behavior of teachers during the learning process at SD Negeri 20 Dadok Tunggul Hitam. The study employed a descriptive qualitative approach, collecting data through a four-point Likert scale questionnaire, which consisted of four aspects: interpersonal communication, openness and empathy, message effectiveness, and feedback provision. The analysis results reveal that teachers possess strengths in their relational foundation, empathy, and clarity of material delivery. However, critical weaknesses were identified that impede the learning process, namely the inconsistency in providing feedback, an indication of disregarding student opinions during discussions, and the use of negative nonverbal communication (such as a harsh tone) during discipline enforcement. This finding confirms a significant gap between communicative awareness and practical pedagogical implementation. Therefore, intervention focusing on strengthening assertive communication competence and developing a structured feedback system is necessary to enhance participatory and sustainable learning quality.